On the occurrence of caligids (Copepoda: Siphonostomatoida) in the marine plankton: a review and checklist - Maran, Balu Alagar Venmathi; Suárez-Morales, Eduardo; Ohtsuka, Susumu; Soh, Ho Young; Hwang, Ui Wook (Zootaxa, 2016)
Members of the copepod genus Caligus Müller, 1785 (Siphonostomatoida: Caligidae) are commonly referred to as sea lice. Virtually all of the more than 450 species utilize marine fishes as hosts, however, an increasing number of records from marine plankton samples shows that at least some species reside in the water column during their adult phase. Members of three different genera, Caligus, Lepeophtheirus von Nordmann, 1832, and Metacaligus Thomsen, 1949 have been reported from plankton samples off eastern Asia and in the north-western Atlantic. Thirteen species have so far been consistently reported from the plankton only with no information on their hosts. Here we review the various hypotheses previously proposed to explain the presence of caligids in the water column, i.e. accidental occurrence, behavioral detachment from the host during mate location, and host-switching. The discovery of adults of two species of Caligus with no other developmental stages on their teleost hosts, suggests an ontogenetic host-switching after the final molt since both species also occurred in plankton samples. A checklist of all caligid records from the marine plankton, including known host data, is presented.